A monetary policy framework for the European Central Bank to deal with uncertainty - Gregory Claeys; Maria Demertzis; Jan Mazza (Bruegel, 2018)
Central banks face new challenges. First, the potential long-term decline in neutral rates of interest in advanced economies could reduce the space for central banks to make policy-rate cuts. Second, the potential flattening of the Phillips curve (ie the weakening of the relationship between inflation and unemployment) in recent decades could reduce the ability of central banks to reach their inflation targets. Third, the discussion on whether central banks should also target financial stability has re-emerged as a result of the crisis. Fourth, the euro-area architectural framework remains incomplete. The problematic interaction between nineteen different fiscal policies and a common monetary policy, the lack of a stabilisation tool and differences in national macro-prudential frameworks would all suggest significant reforms are needed in these realms to strengthen the overall resilience of the system. However, the probability of seeing material changes before the next recession is relatively low, thus presumably leaving the European Central Bank's pivotal role unchanged. More generally, fundamental uncertainty surrounding concepts at the core of the economy, and therefore demand management, has emerged. Monetary policy has to navigate without full knowledge of what the post-crisis 'new normal' is going to be. In light of these considerations, we recommend that the ECB should update its definition of price stability to target core inflation around two percent per year (allowing a tolerance band on either side of the two percent target), on average, over a longer time horizon. Compared to other proposals (such as increasing the targeted inflation level or price-level targeting), our recommendation has the advantage of not departing drastically from the current inflation target and is therefore easier to communicate. In our view, monetary policy should not target financial stability. Other more targeted (and country-specific) tools should be deployed to avoid the build-up of financial stability risks. Closer coordination with national macroprudential authorities and greater harmonisation in the use of macroprudential policies are however strongly recommended, as it is now acknowledged that financial and monetary policies are closely interlinked.
Keywords: 330